2019
DOI: 10.1186/s12873-019-0267-9
|View full text |Cite
|
Sign up to set email alerts
|

Women’s experience of unplanned out-of-hospital birth in paramedic care

Abstract: Background Healthcare literature describes predisposing factors, clinical risk, maternal and neonatal clinical outcomes of unplanned out-of-hospital birth; however, there is little quality research available that explores the experiences of mothers who birth prior to arrival at hospital. Methods This study utilised a narrative inquiry methodology to explore the experiences of women who birth in paramedic care. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 20 publications
0
12
0
7
Order By: Relevance
“…No momento do parto, efetuados em sua maioria por equipes de socorro pré-hospitalar, as mulheres relatam vivências tanto negativas, quanto satisfatórias. As negativas, não se relacionavam com a falta de habilidade e competência obstétrica por parte dos paramédicos, mas com o atendimento pouco afetuoso e humano que receberam durante o evento obstétrico, ao tratamento pouco empático, ao excesso de protocolos e técnicas e a ausência de comunicação entre profissionais e pacientes, tornando o suporte obstétrico um ato mecânico, como fica evidente na fala de uma das mães que participou da pesquisa sobre a ausência de comunicação entre equipe e parturiente, sentindo que os paramédicos estavam ali apenas para fazer o seu trabalho, esquecendo que aquele momento pode ser o de maior angústia na vida de uma mulher 11,12 .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…No momento do parto, efetuados em sua maioria por equipes de socorro pré-hospitalar, as mulheres relatam vivências tanto negativas, quanto satisfatórias. As negativas, não se relacionavam com a falta de habilidade e competência obstétrica por parte dos paramédicos, mas com o atendimento pouco afetuoso e humano que receberam durante o evento obstétrico, ao tratamento pouco empático, ao excesso de protocolos e técnicas e a ausência de comunicação entre profissionais e pacientes, tornando o suporte obstétrico um ato mecânico, como fica evidente na fala de uma das mães que participou da pesquisa sobre a ausência de comunicação entre equipe e parturiente, sentindo que os paramédicos estavam ali apenas para fazer o seu trabalho, esquecendo que aquele momento pode ser o de maior angústia na vida de uma mulher 11,12 .…”
Section: Resultsunclassified
“…São Leopoldo, 2022. Ademais, queixas em relação à realização de procedimentos sem informar ou transmitir confiança ao paciente foram observadas, como segue exemplos de relatos via telefone no qual as mulheres queixam-se de situações em que os técnicos de enfermagem não esperam o alívio das contrações momentâneas para iniciarem a busca por acesso venoso, ignorando que aquela é uma ocasião que promove uma dor intensa, sendo necessário que em algumas ocasiões, a própria paciente tenha que solicitar calma e paciência para o profissional 11 .…”
Section: Quadrounclassified
“…Neonates born in an unplanned setting have high rates of respiratory distress, hypoglycemia, and hypothermia, contributing to a considerably greater chance of requiring admission to special care nurseries or intensive care units (ICUs) than do neonates from similar in-hospital births [ 1 3 , 7 , 8 ]. In comparison with in-hospital deliveries, OHDs are associated with a higher rate of maternal complications, including extensive lacerations of the birth canal, uterine rupture, and post-partum hemorrhage [ 9 – 12 ]. Khupakonke et al also demonstrated LBW to be a predicting factor of OHD [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study is to explore the women's experience of unplanned out-of-hospital birth in Queensland, Australia. This study is part of a larger study that explores the experience of unplanned out-of-hospital birth in paramedic care [1], therefore each woman birthed with paramedic attendance.…”
Section: Introductionmentioning
confidence: 99%